Potential antioxidants from crude extracts of roselle seeds and cashew nut shells for biodiesel storage stability improvement - Hasan, M.H.; Adzib, M.S.M.; Ilham, Zul (American Institute of Physics, 2019)
Biodiesel or fatty acid methyl ester (FAME) is a green alternative fuel that degrades under long-term storage. Antioxidants are utilized in maintaining the oxidation stability of biodiesel by inhibiting the propagation of free radicals resulting in prolonged shelf life. Usage of natural antioxidants from renewable resources is preferred to sustain a green economy and potentially match synthetic antioxidants without being hazardous to the environment. In this study, the potential of antioxidants from crude extracts of Roselle seeds (Hibiscus sabdariffa) and cashew nut shells (Anacardium occidentale) which are agricultural residues that are commonly left unconsumed has been tested for biodiesel storage stability improvement. ABTS antioxidation test on both plant parts showed significant results for all samples regardless of their polarity while β-Carotene test favored polar samples. Positive correlation of DPPH test and total phenolic content (TPC) test confirmed the antioxidant activity of phenolic compounds in all samples. Total flavonoid content (TFC) test also showed positive results for all samples. GC-MS and LC-MS profiling of both plant parts revealed that all samples contained phenolic compounds with the exception of roselle seeds extracted with hexane (RH), which contained mostly fatty acids. Oxidative stability test using Rancimat test showed that polar samples have superior performance than nonpolar samples whereas 3-pentadecyl phenol showed a poor performance in improving biodiesel storage stability.